Sensitivity Analysis of Digital Elevation Model In The Use of Hydrological Applications - Sahid, Sahid; Ihsan, Haikal Muhammad; Saefulloh, Muhammad Abia; Ulhaq, Wiedad Diya (Universitas Trunojoyo Madura, 2024)
Assessing DEMs is a critical step in hydrological applications to reduce uncertainties. This study assesses the uncertainty level of using several DEM products by comparing the derivation of watershed morphometric information in the form of hydrological boundaries, river flow networks, and meeting points between river networks. This research assessed three DEM products, namely SRTM, ASTER GDEM, and NASADEM, with the topographic map as reference data for product assessment. The evaluation is based on two criteria: DEM product assessment and morphometric extraction. The second criterion assessment compared river morphometry products from several parameters, including watershed area, river network density, and river network meetings. The analysis results showed that in the first criterion, the NASADEM product was the product with the closest RMSE and PBIAS values to the reference data. Further assessment of river morphometry products shows that the ASTER GDEM watershed area parameter has the closest area value. In the horizontal accuracy parameter of river network products, NASADEM has the smallest average error value. Furthermore, in the accuracy assessment in determining the meeting between tributaries and the main river and the density of river flow, SRTM is the closest compared to other DEM products. The vertical and horizontal accuracy of DEM must be considered before using in hydrologic applications.